The three month's dietary brown rice intervention has not significantly decreased levels of CRP, TNF- α, and IL6 of type 2 diabetes mellitus patients - Fajar Ari Nugroho; Inggita Kusumastuty; Anggun Rindang Cempaka; Atifa Nafia Hasantie Latif; Dian Handayani (Healthcare in Low-resource Settings, 2023)
Introduction: The increased quantities of inflammatory biomarkers such as C-Reactive Proteins (CRP), Tumour Necrosis Factor-α (TNF-α), and Interleukin-6 (IL-6) have been reported to be associated with an increased risk of metabolic syndrome including type 2 diabetes mellitus (T2DM). However, brown rice is an alternative dietary food source that is known to have many health benefits including high fibre content. In addition to fibre, brown rice is also reported to have moderate amounts of proteins, unsaturated lipids, several minerals, and a lot of bioactive substances that are highly beneficial to health. This study aims to prove the role of brown rice dietary intervention in the reduction of inflammatory biomarkers in type 2 diabetes mellitus patients.